Tailored gamification and serious game framework based on fuzzy logic for saving energy in connected thermostats. (20th July 2020) - Ponce, Pedro; Meier, Alan; Méndez, Juana Isabel; Peffer, Therese; Molina, Arturo; Mata, Omar
Abstract: Connected thermostats (CTs) often save less energy than predicted because consumers may not know how to use them and may not be engaged in saving energy. Additionally, several models perform contrary to consumers' expectations and are thus not used the way they are intended to. As a result, CTs save less energy and are underused in households. This paper reviews aspects of gamification and serious games focused on engaging consumers. A gamification and serious games framework is proposed for saving energy that is tailored by a fuzzy logic system to motivate connected thermostat consumers. This intelligent gamification framework can be used to customize the gamification and serious game strategy to each consumer so that fuzzy logic systems can be adapted according to the requirements of each consumer. The framework is designed to teach, engage, and motivate consumers while helping them save electrical energy when using their thermostats. It is described the proposed framework as well as a mockup that can be run on a cellphone. Although this framework is designed to be implemented in CTs, it can be translated to their energy devices in smart homes. Highlights: Personalized interfaces engage users to reduce energy consumption in households. Gamification in a fuzzy logic system allows tailored Human Machine Interfaces. Behavior problems in thermostats have a solution with gamification interfaces. Personality traits are related to energy behavior and role players. Shaping users' behavior by tailored products based on users' characteristics.